Patent landscape analysis of rare earth extraction: Innovations, challenges, and geopolitical implications - Nurul Ain, Ismail; Siti Nor Amanina, Said (Springer, 2025)
This paper analyzes the rare-earth extraction patent landscape, highlighting rapid technological advancements and global investments. This study highlights China’s dominant position in patent activity, driven by robust governmental support and a focus on advanced hydrometallurgical methods and separation techniques. The United States, Japan, and Russia also contribute significantly, each with distinct technological focuses, ranging from sustainable extraction methods to high-purity separation processes and innovative extraction devices. The analysis identifies key trends in the development of new extraction agents, advanced monitoring systems, and improved waste treatment technologies, reflecting the industry’s shift towards environmental sustainability and operational efficiency. However, the relatively low patent scores in some emerging areas indicate a need for broader adoption and optimization. As demand for rare-earth elements continues to grow, driven by their critical role in high-tech and green energy applications, this paper underscores the importance of securing and advancing extraction technologies. This paper recommends strategies for stakeholders to ensure a sustainable and secure REE supply through innovation and investment.